Combination Effect of Slow Interval Training and Lemongrass Ethanol Extract (Cymbopogon citratus) on Body Weight and Fat Mass in Male Wistar Rats (Rattus norvegicus Sp) Obesity Model - Siahaan, Sulyaprilawati Battri; Machrina, Yetty; Widyawati, Tri; Rusdiana, Rusdiana; Savira, Maya (Journal of Biomedicine and Translational Research, 2025)
Background: Obesity, a global health crisis affecting over 890 million adults, requiring effective and safe management strategies. Lifestyle-based interventions, such as physical exercise and herbal supplementation, provide promising non-invasive alternatives. Slow Interval Training (SIT) improves fat metabolism with low injury risk, while lemongrass (Cymbopogon citratus) contains bioactive compounds with anti-obesity potential.Objective: This study investigates the combined effects of SIT and lemongrass ethanol extract on body weight and fat mass in a high-fat diet (HFD)-induced obese male Wistar rat model.Methods: Thirty-five male Wistar rats were divided into five groups: healthy control, obese control, SIT only, lemongrass extract only, and SIT + lemongrass. Obesity was induced through a high-fat diet before intervention. Body weight was measured weekly, and fat mass was analyzed after eight weeks of treatment.Results: Obese controls showed significant weight gain (p<0.001). The lemongrass-only group showed a 12.7% weight reduction, while the combination group achieved the lowest final weight (200 g) and the lowest fat mass (2.39 g, p=0.048). Significant intergroup differences appeared from week 1 and persisted until week 13 (p<0.05). The combination group maintained stable weight after intervention, outperforming SIT or lemongrass alone.Conclusion: The combination of SIT and lemongrass ethanol extract significantly reduces body weight and fat mass in obese rats, demonstrating synergistic efficacy. Lemongrass inhibits fat absorption and enhances metabolic regulation, while SIT promotes fat oxidation. This dual approach offers a viable, non-invasive strategy for obesity management, warranting further clinical exploration.